2002
DOI: 10.1161/01.res.0000018003.14304.e2
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of Ca v 1.3 (α 1D ) Calcium Channel in Sinoatrial Nodes

Abstract: Abstract-We directly examined the role of the Ca v 1.3 (␣ 1D ) Ca 2ϩ channel in the sinoatrial (SA) node by using Ca v 1.3 Ca 2ϩ channel-deficient mice. A previous report has shown that the null mutant (Ca v 1.3 Ϫ/Ϫ ) mice have sinus bradycardia with a prolonged PR interval. In the present study, we show that spontaneous action potentials recorded from the SA nodes show a significant decrease in the beating frequency and rate of diastolic depolarization in Ca v 1.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
114
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(125 citation statements)
references
References 33 publications
11
114
0
Order By: Relevance
“…In addition, Ca v 1.3 −/− mice reproduce severe AV dysfunction typical of human congenital heart block (16). Previous studies demonstrated that Ca v 1.3-mediated I Ca,L plays a major role in the determination of heart rate and impulse conduction in mice and humans (10,11,14,16,17,19). However, despite the importance of Ca v 1.3-mediated I Ca,L in determining the rate of the diastolic depolarization in isolated SAN and AV node myocytes (14,16), it was unclear how Ca v 1.3 loss of function translates into SSS in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Ca v 1.3 −/− mice reproduce severe AV dysfunction typical of human congenital heart block (16). Previous studies demonstrated that Ca v 1.3-mediated I Ca,L plays a major role in the determination of heart rate and impulse conduction in mice and humans (10,11,14,16,17,19). However, despite the importance of Ca v 1.3-mediated I Ca,L in determining the rate of the diastolic depolarization in isolated SAN and AV node myocytes (14,16), it was unclear how Ca v 1.3 loss of function translates into SSS in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, severe AV dysfunction is recorded in Ca v 1.3 −/− mice to variable degrees. Typically, these mice show first-and second-degree AV block (16,17,19). Complete AV block with dissociated atrial and ventricular rhythms can also be observed in these animals.…”
Section: Significancementioning
confidence: 95%
“…To examine this, ECGs were recorded following administration of propranolol and atropine to block β-adrenergic and muscarinic receptors, respectively [28]. Following autonomic block, the R wave amplitude and P, QRS, and PR durations remained similar between mice of all three genotypes (Table 2), although compared to control recordings the administration of propranolol and atropine resulted in longer P (by ~1 ms) and QRS (~ 0.5-2 ms) components (Table 2).…”
Section: Surface Ecg Recordingsmentioning
confidence: 99%
“…Ventricular cardiac L-type Ca 2ϩ channels are predominantly formed by the Ca v 1.2 subunit, which is also expressed at high levels in atria (5,27). Ca v 1.3 subunits, which are only expressed in atria at much lower levels than Ca v 1.2 subunits, control pacemaker activity (19,36). Whether RhoA also regulates the activity of Ca v 1.2 and Ca v 1.3 channels in atrial myocytes is worth additional investigation.…”
Section: Discussionmentioning
confidence: 99%